2008
DOI: 10.1158/1055-9965.epi-07-2855
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Questionnaire to Measure Colorectal Cancer Screening Behaviors: Does Mode of Survey Administration Matter?

Abstract: Valid and reliable self-report measures of cancer screening behaviors are important for evaluating efforts to improve adherence to guidelines. We evaluated test-retest reliability and validity of selfreport of the fecal occult blood test (FOBT), sigmoidoscopy (SIG), colonoscopy (COL), and barium enema (BE) using the National Cancer Institute colorectal cancer screening (CRCS) questionnaire. A secondary objective was to evaluate reliability and validity by mail, telephone, and face-to-face survey administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 41 publications
5
91
1
Order By: Relevance
“…However, the study's cross-sectional design and reliance on self-reported screening limit the KNCSS. Previous studies have indicated that self-reported FOBT screening data might result in overestimates of the proportion screened [26,27], and recent research has suggested that over-reporting may be greater for FOBT than for endoscopy [28]. Therefore, the proportion of subjects who were actually up-to-date for CRC testing may be lower than that indicated by the current analysis.…”
Section: Discussionmentioning
confidence: 57%
“…However, the study's cross-sectional design and reliance on self-reported screening limit the KNCSS. Previous studies have indicated that self-reported FOBT screening data might result in overestimates of the proportion screened [26,27], and recent research has suggested that over-reporting may be greater for FOBT than for endoscopy [28]. Therefore, the proportion of subjects who were actually up-to-date for CRC testing may be lower than that indicated by the current analysis.…”
Section: Discussionmentioning
confidence: 57%
“…Persons who did not respond may have different patterns of screening or diabetes risk behaviors and risk factors. Moreover, because the data are self-reported, there may be recall bias or over-reporting of health behaviors [46]. The analyses were largely descriptive and because of the limited sample sizes in some stratified analyses, some comparisons may have been underpowered to detect differences that may exist between subgroups or differences in screening by diabetes risk behaviors and risk factors.…”
Section: Limitationsmentioning
confidence: 99%
“…However, that limitation would be similar for all respondents. Many studies have concluded that self-reporting is fairly accurate, showing good or fair concordance and overall agreement with administrative health data [15][16][17][18] . Estimates from an earlier study on breast cancer screening in Canada 19 (based on administrative data), of the proportion of women 50-69 years of age who underwent bilateral mammography within and outside organized programs in a 24-month period, closely resemble the cchs self-reported screening rates.…”
Section: Discussionmentioning
confidence: 99%